THE PROMISE AND PERILS OF CONNECTEDNESS: LIVING IN A NEW VIRTUAL WORLD. - Clough, William R. (Journal of Interdisciplinary Studies, 2021)
Social media facilitate and intensify communication to an unprecedented degree and humanity is adjusting to this new state of affairs. Internet connectivity enables the human desire for sociality, personal relationships, and social acceptance to a remarkable degree. But human communication evolved in a face-to-face world, where people experienced one another as well as hearing one another. Modern communication has removed the interpersonal experience factor, leaving people to interpret the messages, not of flesh-and-blood individuals but of stereotypes, beliefs about a general class of people. This essay surveys some classic understandings of communication, followed by analysis of some of the characteristics and pitfalls of social media. It concludes that social media are a huge change in human communication requiring personal and society-wide adjustments based on principles that have stood the test of time, including selfawareness, self-control, and care to take the moral and interpersonal high road in online communications.